Evaluating Universal Design for Learning and Active Learning Strategies in Biology Open Educational Resources (OERs) (Teaching and Learning Inquiry, 2024)
With the onset of COVID-19, colleges and universities moved to emergency remote teaching, and instructors immediately adjusted their curricula. Many instructors adapted or developed new online lessons that they subsequently published as Open Educational Resources (OERs). While much has been examined related to how entire course designs evolved during this period, the same attention has not been paid to how individual lessons were structured to meet online learners’ needs. As such, we evaluated OER lessons for the integration of universal design for learning (UDL) guidelines and active learning strategies. We evaluated OER lessons published in CourseSource, which is an open-access, peer-reviewed journal that focuses on biology lessons implemented in undergraduate classrooms and provides the necessary details and supporting materials to replicate the lesson. We found that biology instructors used a variety of UDL guidelines and active learning strategies to encourage student learning and engagement in online teaching environments. This study also provides a collection of OER online lessons that instructors and educational developers can use to inform the practice of engaging biology students.Read the corresponding ISSOTL blog post here.